Wave diffraction and near-trapping by a multi-column gravity-based structure - Walker, D; Eatock Taylor, R; Taylor, P; Zang, J (2008)
This paper is concerned with the diffraction of water waves by offshore structures, with the ultimate aim of proposing tools for guiding airgap design. The diffraction of monochromatic waves by an array of four bottom mounted cylinders and a gravity-based structure is studied in detail using linear and second order theory. The phenomenon of near-trapping is investigated, allowing guidelines for airgap design to be established. When contemplating airgap design, however, it is crucially important that consideration is given to the largest waves in a sea state. Therefore, in this study a design wave, called NewWave, is proposed as a realistic model for large ocean waves and is used as the incident wave field in the wave-structure diffraction analysis. © 2007 Elsevier Ltd. All rights reserved.